2020
DOI: 10.1016/j.joto.2020.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to blast shock waves via the ear canal induces deficits in vestibular afferent function in rats

Abstract: The ears are air-filled structures that are directly impacted during blast exposure. In addition to hearing loss and tinnitus, blast victims often complain of vertigo, dizziness and unsteady posture, suggesting that blast exposure induces damage to the vestibular end organs in the inner ear. However, the underlying mechanisms remain to be elucidated. In this report, single vestibular afferent activity and the vestibulo-ocular reflex (VOR) were investigated before and after exposure to blast shock waves (∼20 PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…The present mechanical model was also applied to estimate utricular hair bundle deflection caused by blast exposure. It has been shown in rodents that a bilateral 63 kPa (~190 dB) blast results in eardrum perforations and likely permanent loss of stereocilia in the utricle ( 48 ), and a 137 kPa (~197 dB) unilateral blast reduces spontaneous discharge and sensitivity of afferents with regular and irregular inter-spike intervals without significant acute loss of steady state VOR ( 49 , 50 ). Humans experience persistent vestibular symptoms and increased incidence of BPPV following blast exposure ( 51 ), consistent with the hypothesis that the otolith organs are uniquely vulnerable to blast injury ( 52 ), putatively due to the close proximity of the utricle to the stapes ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present mechanical model was also applied to estimate utricular hair bundle deflection caused by blast exposure. It has been shown in rodents that a bilateral 63 kPa (~190 dB) blast results in eardrum perforations and likely permanent loss of stereocilia in the utricle ( 48 ), and a 137 kPa (~197 dB) unilateral blast reduces spontaneous discharge and sensitivity of afferents with regular and irregular inter-spike intervals without significant acute loss of steady state VOR ( 49 , 50 ). Humans experience persistent vestibular symptoms and increased incidence of BPPV following blast exposure ( 51 ), consistent with the hypothesis that the otolith organs are uniquely vulnerable to blast injury ( 52 ), putatively due to the close proximity of the utricle to the stapes ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lien and Dickman (37) exposed mice to a 63 kPa peak blast-wave over pressure and observed the following post-exposure changes: (1) significant loss of hair cell stereocilia in the cristae and macule up to one-month post-exposure, and (2) significant reduction in horizontal VOR gain and phase lags that lasted many weeks following a single blast exposure event. Yu et al (43) exposed anesthetized rats to blast shock waves (∼20 PSI) delivered to the external canal and observed a significant reduction in the spontaneous discharge rates of the otolith and canal afferents and a reduction in the sensitivity of irregular canal afferents to sinusoidal head rotation at 0.5 to 2 Hz. In contrast to the findings of Lien and Dickman (37), Yu et al (43), observed few changes in the VOR responses to sinusoidal head rotation and translation.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al (43) exposed anesthetized rats to blast shock waves (∼20 PSI) delivered to the external canal and observed a significant reduction in the spontaneous discharge rates of the otolith and canal afferents and a reduction in the sensitivity of irregular canal afferents to sinusoidal head rotation at 0.5 to 2 Hz. In contrast to the findings of Lien and Dickman (37), Yu et al (43), observed few changes in the VOR responses to sinusoidal head rotation and translation.…”
Section: Discussionmentioning
confidence: 99%